Revitalization of Marginal Land Utilization from Former Coal Mining in Nagari Muaro Sopan, Padang Laweh District, Dharmasraya Regency - Sri Sulastri; Juprianto; Jamilah; Osronita (Jurnal Ragam Pengabdian, 2026)
Open-pit coal mining in Nagari Muaro Sopan, Padang Laweh District, Dharmasraya Regency, has generated extensive marginal land characterized by severe environmental degradation, vegetation loss, and soil contamination. This study investigates comprehensive revitalization strategies for post-mining landscapes through systematic literature review and field observation. Secondary data were collected from peer-reviewed scientific journals, government reports, and reclamation case studies, complemented by primary field observations at mining sites in Nagari Muaro Sopan. Thematic analysis identified seven critical strategies for effective post-mining land revitalization: (1) comprehensive land condition assessment, (2) soil quality restoration through organic amendment and pH adjustment, (3) drainage infrastructure development and water management systems, (4) appropriate native vegetation establishment, (5) ecosystem and biodiversity recovery, (6) local community empowerment through capacity building, and (7) sustainable economic development initiatives. Results demonstrate that integrated implementation of these strategies can substantially mitigate environmental degradation, enhance disaster resilience, and generate sustainable economic benefits for surrounding communities. The study emphasizes that successful revitalization fundamentally requires multi-stakeholder collaboration involving government agencies, mining corporations, and local communities. This framework provides practical guidance for transforming degraded post-mining landscapes into productive, ecologically stable, and economically viable systems in Indonesian contexts.